2018
DOI: 10.14693/jdi.v25i1.1124
|View full text |Cite
|
Sign up to set email alerts
|

Comet Assay Assessment of DNA Damage in Buccal Mucosa Cells Exposed to X-Rays via Panoramic Radiography

Abstract: Ionizing radiation (IR) presents a risk to human health via DNA damage even when administered at low doses, such as those used in panoramic radiography. Objectives: This study used the comet assay to assess DNA damage in buccal mucosa cells consequent to X-ray radiation from panoramic radiography. Methods: Twenty participants were recruited from among patients who underwent panoramic examinations at Prof. Soedomo Dental Hospital, Universitas Gadjah Mada, and divided into two groups of 10. Buccal mucosa cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Comet assay data suggest that a radiography scan results in a significant increase in DNA DSBs in adults. 131 Similar data were obtained from children. 50 To our knowledge, these are the only two studies that reported on this and therefore should be interpreted with caution, given the many observed contradictions from the other assays that are described in this section.…”
Section: Plain Dentomaxillofacial Radiographysupporting
confidence: 56%
“…Comet assay data suggest that a radiography scan results in a significant increase in DNA DSBs in adults. 131 Similar data were obtained from children. 50 To our knowledge, these are the only two studies that reported on this and therefore should be interpreted with caution, given the many observed contradictions from the other assays that are described in this section.…”
Section: Plain Dentomaxillofacial Radiographysupporting
confidence: 56%
“…Most imaging techniques in the dental and medical examination have utilized X-ray radiography, which may induce adverse biological changes related to the oxidative reaction after ionizing radiation exposure in living tissues. 34,35 Instead of using ionizing radiation in X-ray radiography, PAI utilizes non-ionizing laser irradiation as an EM source. 15 However, we found that studies in PA image quality are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…The inner lining of the cheeks, known as the buccal mucosa, is an area that can develop cancer. Buccal mucosal cancer is a rare and dangerous form of oral cancer that makes up a small percentage of patients diagnosed with mouth cancer [ 97 ]. There is a correlation between local relapse and margin condition for both small and large buccal cancers that are treated only with surgery; however, adjuvant therapy can improve local control in early stage buccal cancers [ 98 ].…”
Section: Region-based Oral Cancermentioning
confidence: 99%